Case Report: Hereditary Alpha Tryptasemia in Children: A Pediatric Case Series and a Brief Overview of Literature - Zama, Daniele; Muratore, Edoardo; Giannetti, Arianna; Neri, Iria; Conti, Francesca; Magini, Pamela; Ferrari, Simona; Pession, Andrea (Frontiers in Pediatrics, 2021)
Hereditary alpha tryptasemia (HαT) is a recently described autosomal dominant genetic trait caused by an increased copy number of the TPSAB1 gene. It commonly leads to elevated basal serum tryptase levels, and it is associated with heterogeneous clinical manifestations. Some individuals report few to no symptoms, while others present with a spectrum of debilitating features. Most symptoms related to HαT may be explained by mast cell activation and mediator release, namely multiple allergies, anaphylaxis, and skin rash. However, the genotype-phenotype correlation has not yet been clearly understood. In particular, the characterization of the clinical spectrum lacks in children, where differential diagnosis could be challenging. Systemic mastocytosis, HαT, and mast cell activation syndrome are all associated with overlapping pathophysiology and symptoms, making the distinction between these conditions a difficult task. We herein describe two pediatric cases of HαT and their respective families at our tertiary care teaching hospital, highlighting the diagnostic workup and differential diagnosis. We also provide a brief review of the literature to underline the peculiar features of this condition in children.